Cu3MS4 (M=V, Nb, Ta) and its Solid Solutions with Sulvanite Structure for Photocatalytic and Photoelectrochemical H2 Evolution under Visible‐Light Irradiation. Issue 9 (15th February 2019) - Ikeda, Satoru; Aono, Naruhiko; Iwase, Akihide; Kobayashi, Hisayoshi; Kudo, Akihiko
Abstract: Solid solutions with of Cu3 VS4 with either Cu3 NbS4 or Cu3 TaS4 (Cu3 Nb1− x V x S4 or Cu3 Ta1− x V x S4 ) were prepared by a solid‐state reaction and adopted a sulvanite structure. Their band gaps were 1.6–1.7 eV corresponding to the absorption of a wide range of visible light. Ru cocatalyst‐loaded Cu3 MS4 (M=V, Nb, Ta), Cu3 Nb1− x V x S4, and Cu3 Ta1− x V x S4 showed photocatalytic activities for sacrificial H2 evolution under visible‐light irradiation. Most solid solutions showed better activities than the single‐component Cu3 MS4 (M=V, Nb, Ta). Cu3 MS4 (M=V, Nb), Cu3 Nb1− x V x S4, and Cu3 Ta1− x V x S4 also functioned as photoelectrodes and gave cathodic photocurrents under visible‐light irradiation, indicating a p‐type semiconductor character. Cu3 Nb0.9 V0.1 S4 showed the best photocatalytic and photoelectrochemical performances. When Ru‐loaded Cu3 Nb0.9 V0.1 S4 was used as a photocathode with a CoO x ‐loaded BiVO4 photoanode, photoelectrochemical water splitting proceeded under simulated sunlight irradiation without an external bias. Abstract : A solid solution to the problem : Cu3 M1− x V x S4 (M=Nb, Ta) solid solutions with a sulvanite structure have arisen as visible‐light‐responsive photocatalysts and photocathodes for H2 evolution. When Ru/Cu3 Nb0.9 V0.1 S4 was used as a photocathode combined with a CoO x /BiVO4 photoanode, photoelectrochemical water splitting proceeded under simulated sunlight irradiation without an external bias.